2001
DOI: 10.1128/jvi.75.10.4922-4928.2001
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Primer Binding Site-Mutated Simian Immunodeficiency Virus Vectors by Genetically Engineered Artificial and Hybrid tRNA-Like Primers

Abstract: Simian immunodeficiency viruses (SIV) harbor primer binding sites (PBS) matching tRNA 3Lys or tRNA 5 Lys . To study determinants of primer usage in SIV, a SIVmac239-based vector was impaired by mutating the PBS to a sequence (PBS-X2) with no match to any tRNA. By cotransfection of a synthetic gene encoding a tRNA Pro -like RNA with a match to PBS-X2, the activity of this vector could be restored to a transduction efficiency slightly lower than that of the wild-type vector. A vector with a PBS matching tRNA Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…PBMC, peripheral blood mononuclear cell. Although we cannot formally exclude replication of SCIV in vivo, we consider this to be highly unlikely since (i) the primer complementation approach used to generate the SCIVs reduces infectivity in single-round replication assays at least 10 4 -fold (17,18); (ii) the SCIVs have an additional deletion of vif, which severely impairs replication in primary cells and rhesus macaques (9,32), and (iii) we were never able to recover replication-competent virus from SCIV-injected animals despite repeated attempts (23).…”
Section: Discussionmentioning
confidence: 99%
“…PBMC, peripheral blood mononuclear cell. Although we cannot formally exclude replication of SCIV in vivo, we consider this to be highly unlikely since (i) the primer complementation approach used to generate the SCIVs reduces infectivity in single-round replication assays at least 10 4 -fold (17,18); (ii) the SCIVs have an additional deletion of vif, which severely impairs replication in primary cells and rhesus macaques (9,32), and (iii) we were never able to recover replication-competent virus from SCIV-injected animals despite repeated attempts (23).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that replication of Akv-MLVderived vectors with a mutationally impaired PBS can be restored by engineered complementary tRNA primers ( Fig. 1A), functional in both the initiation of first-strand synthesis and second-strand transfer (Lund et al, 1997;Modin et al, 2000;Hansen et al, 2001). In this setup (producer-cell complementation) vector construct and tRNA primer expressing constructs are cotransfected into the BOSC 23 packaging cell line ( Fig.…”
Section: Experimental Designmentioning
confidence: 99%
“…tRNA X2pro and tRNA X2Lys3 , both able to complement the Akv-MLV-derived vector pPBS-x2m (Hansen et al, 2001) in the producer-cell complementation system, were transfected (with a transfection efficiency of approximately 30%) into NIH 3T3 cells to verify expression of the synthetic tRNAs.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional mechanisms that might contribute to mobilization of SIN vectors are promoter trapping by integration of the lentiviral vector downstream of an active cellular promoter and recombination events leading to the reconstitution of a transcriptional active 3Ј U3 region of the lentiviral vector during vector production. Mutation of the primer binding site (PBS) of an SIV vector and complementation of the PBS mutations during vector production by a matched artificial tRNA provided an independent approach to reduce the risk of SIV vector mobilization by HIV-1 (8,9). However, mobilization of the SIV vector by homologous SIV was reduced to a lesser extent.…”
mentioning
confidence: 99%